(untitled) (Research, Society and Development, 2023)
The dentigerous cyst is an alteration originated by the separation of the pericoronal follicle from any non-erupted dental elements, being the most common type of developmental odontogenic cysts. These cysts can acquire considerable volume resulting in facial asymmetry, and may or may not be septic. Radiographically, dentigerous cysts have a unilocular radiolucent aspect with well-defined margins associated with the crown of the included element, which may give the impression of multilocular aspects in large cysts. The dentigerous cyst has 3 radiographic variations: Central (most common), Lateral and Circumferential. Its treatment ranges from enucleation to marsupialization, with an excellent prognosis for the overwhelming majority of cysts and with rare recurrence, however it can undergo a neoplastic transformation to an ameloblastoma. The objective of this study is to present a case report of the enucleation of a dentigerous cyst in the mandible, of great extension, in the posterior region of the left side, associated with tooth 38, with the need for rigid internal fixation after removal of the lesion, in a patient 59-year-old male with leucoderma, showing its clinical, imaging and histopathological properties and its form of treatment. It is concluded that surgical excision of the dentigerous cyst is the main treatment choice and, associated with rigid internal fixation, when indicated, results in a better prognosis for the patient.